The Science of Service Systems - Demirkan, Haluk; Sphohrer, James C.; Krishna, Vikas (Service Science: Research and Innovations in the Service Economy,1865-492440, 2011)
The Science of Service Systems intends to stimulate discussion and understanding by presenting theory-based research with actionable results. Most of the articles focus on formalizing the theoretical foundations for a science of service systems, examining a wide range of substantive issues and implementations related to service science from various perspectives. From the formal (ontologies, representation specifications, decision-making and maturity models) to the informal (analysis frameworks, design heuristics, anecdotal observations), these contributions provide a snapshot in time of the gradually emerging scientific understanding of service systems. The Science of Service Systems, along with its companion text, Service Systems Implementation, is designed to present multidisciplinary and multisectoral perspectives on the nature of service systems, on research and practice in service, and on the future directions to advance service science. These two volumes compose a collection of articles from those involved in the emerging area known as service science.